El software minitab 16 como herramienta de análisis de los datos estadísticos para mejorar la enseñanza aprendizaje en los alumnos de la carrera de ingeniería comercial en el período 2014 - Casa Chiluisa, Paulina Elizabeth (2016)
The technology as a methodological tool in the Superior Education, It is fundamental in the new professional academic formation. The present research work has as an objective the creation of a manual and the elaboration of a practical exercise which serves as a guide to handle the Minitab 16 software in the Commercial Engineering in the 2014 Academic period, as a teaching-learning process guide. In this way. It was proposed this methodological tool in benefit of students and teachers from this career facilitating the comprehension of statistics subject through practical exercises and the statistical data analysis for developing the student´s abilities to make decisions within an area of business….